You Had a Job for Life : Story of a Company Town - Sayen, Jamie (Book collections on Project MUSE., 2023)
"Drawing on conversations with scores of former paper mill workers in Groveton, New Hampshire, Sayen reconstructs the mill's human history and the devastating impact of global capitalism on a small New England town. This is a heartbreaking story of the decimation of industrial America"--